Chapter Valori e tecniche in tema di disciplina dei poteri datoriali - DE LUCA TAMAJO, Raffaele (Studi e saggi, 2022)
The article deals with the controversial topic of the limits in which the immanent "values" in the legal system and especially in the Italian Constitution can affect the operations of interpretation of the norms of positive law. The thesis is that it is not allowed to use a hierarchy of values dictated by the ideological heritage of the interpreter, but only to draw inspiration from the graduation and mediation of interests emerging from the positive legal order, albeit by resorting to the instrument of interpretation in accordance with the Italian Constitution and the European union law.